2012
DOI: 10.1007/s10120-011-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of weekly paclitaxel in patients with advanced gastric cancer refractory to docetaxel-based chemotherapy

Abstract: Weekly paclitaxel was modestly active in patients with gastric cancer refractory to docetaxel-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…There is a clinical study showing that paclitaxel may help alleviate ERCC1-related platinum resistance in ovarian cancer [39]. Cisplatin monotherapy is not commonly used; taxane monotherapy is used to treat advanced gastric cancer [40,41]. Thus, paclitaxel might play a greater role than cisplatin in patients with advanced gastric cancer treated with taxane-cisplatin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clinical study showing that paclitaxel may help alleviate ERCC1-related platinum resistance in ovarian cancer [39]. Cisplatin monotherapy is not commonly used; taxane monotherapy is used to treat advanced gastric cancer [40,41]. Thus, paclitaxel might play a greater role than cisplatin in patients with advanced gastric cancer treated with taxane-cisplatin chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete cross-resistance between PTX and DTX was observed in MCF-7 cells [22], indicating varying degrees of cross-resistance between cancer types. Several clinical analyses also show incomplete cross-resistance between PTX and DTX in breast [23,24], ovarian [25] and gastric cancer [15] patients. Hence, incomplete cross-resistance between PTX and DTX was expected in the present esophageal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, incomplete cross-resistance between these drugs has been indicated in several in vitro and in vivo studies of various cancer types [11,13,14,15]. Accordingly, we assumed incomplete cross-resistance between PTX and DTX in patients with esophageal squamous cell carcinoma, and performed a retrospective study to assess the efficacy and safety of sequential treatments with taxanes in patients with esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In another phase II trial incorporating PTX with S-1, Wang et al [8] reported an overall response rate of 46.3 %. When used as a single agent in patients with docetaxel-refractory advanced GC, PTX also showed certain therapeutic benefit [9,10]. Lately, even more promising results came from a phase II trial of nanoparticle albumin-bound paclitaxel as second-line chemotherapy for unresectable or recurrent gastric cancer, which showed an overall response rate of 27.8 % and disease control rate of 59.3 % [11].…”
Section: Introductionmentioning
confidence: 99%